2010
DOI: 10.1002/lt.22146
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia and the risk of new-onset diabetes after liver transplantation

Abstract: New-onset diabetes after transplantation (NODAT) is a frequent complication after liver transplantation and has a negative impact on both patient and graft survival. In analogy with the previous finding of an association between posttransplant hypomagnesemia and NODAT in renal transplant recipients, the relation between both pretransplant and posttransplant hypomagnesemia and NODAT was studied in liver transplant recipients (LTRs). One hundred sixty-nine adult LTRs (>18 years old) without diabetes who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 31 publications
2
41
1
1
Order By: Relevance
“…A smaller retrospective study revealed similar findings (77). A study in liver transplant recipients also suggested that early posttransplant hypomagnesemia was associated with increased PTDM (78). A small clinical trial of magnesium supplementation was conducted to determine the relative impact of hypomagnesemia on PTDM in CNI-treated kidney transplant recipients.…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 62%
See 1 more Smart Citation
“…A smaller retrospective study revealed similar findings (77). A study in liver transplant recipients also suggested that early posttransplant hypomagnesemia was associated with increased PTDM (78). A small clinical trial of magnesium supplementation was conducted to determine the relative impact of hypomagnesemia on PTDM in CNI-treated kidney transplant recipients.…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 62%
“…First-phase, second-phase, and area-under-the-curve insulin secretion were all lower in CMVpositive recipients (133). CMV infection has also been associated with increased risk for PTDM after liver transplant, although in few studies (78,118). To date, CMV infection has not yet been suggested to be a significant contributing factor for PTDM after heart or lung transplant.…”
Section: Potential Role Of "Stress" Inflammation and Infectionmentioning
confidence: 99%
“…Citations are examples supporting these statements and are not meant to include all references on this topic. Additional references can be found in the comprehensive review by Freeman (5) General indirect effects-elevated risks Bacterial infections (19,134,135) Fungal infection (19,26) Viral infections (summarized in (6)) PTLD (136) Cardiovascular events (137) New-onset diabetes mellitus after transplantation (138,139) Immunosenescence (140) Acute rejection (36,37,134) Mortality (19,134,(141)(142)(143)(144) Transplant-specific indirect effects Chronic allograft nephropathy and/or allograft loss after renal transplant (19,145,146) Accelerated hepatitis C recurrence after liver transplant (147) Hepatic artery thrombosis after liver transplant (144,148,149) Allograft vasculopathy after cardiac transplant (150,151) Bronchiolitis obliterans after lung transplant (37,141,143) hereafter referred to as D+/R−). Preemptive therapy is defined as serial testing done weekly or biweekly for the first few months after transplant or after treatment of rejection, with treatment dose antiviral therapy initiated once a certain defined positive threshold is reached.…”
Section: Universal Prophylaxis and Preemptive Therapymentioning
confidence: 99%
“…The same research group published similar results based on a cohort of 169 liver transplant recipients. 35 The findings of Van Laecke et al…”
Section: Discussionmentioning
confidence: 99%